A Systematic Review and Meta-Analysis of the Efficacy of Kinesio Taping for Pain Management and Pressure Pain Threshold in Myofascial Pain Syndrome - Mahmoud Kandeel; Mohamed Marzok; Sheryar Afzal; Ahmed Meligy; Maryam Mahmoud; Ibrahim Albokhadaim; Khalid M. Al Khodair; Sameer Alhojaily (Pain Research and Management)
Myofascial pain syndrome (MPS) is a prevalent musculoskeletal disorder characterized by myofascial trigger points (MTrPs), which can significantly impact an individual’s quality of life. This study aimed to evaluate the efficacy of Kinesio taping (KT) in reducing pain intensity and increasing pressure pain threshold (PPT) in individuals with MPS. A comprehensive search was performed across five electronic databases (PubMed, Web of Science, Cochrane Library, Embase, and SCOPUS) from inception to May 2024. Randomized controlled trials (RCTs) comparing KT to a control group, including no intervention, placebo, or sham taping, in individuals with MPS were included. Data on pain intensity and PPT were extracted and pooled using RevMan 5.4 software. A total of 15 RCTs were included in the systematic review and meta-analysis. The pooled analysis showed a significant reduction in pain intensity in the KT group compared to the control group immediately after intervention (mean difference [MD] = −1.07, 95% confidence interval (CI) [−1.93, −0.20], p=0.02), within the first week (standardized mean difference [SMD] = −1.44, 95% CI [−2.39, −0.49], p=0.003), and after 2-3 weeks (SMD = −0.97, 95% CI [−1.46, −0.49], p<0.0001). However, the effect diminished after 4–6 weeks (MD = −0.90, 95% CI [−1.65, −0.14], p=0.02). Regarding PPT, KT significantly increased PPT within the first week (MD = 4.32, 95% CI [2.47, 6.16], p<0.00001) but not immediately after intervention or after 2-3 and 4–6 weeks. This meta-analysis provides evidence that KT is effective in reducing pain intensity and increasing PPT in individuals with MPS, particularly in the immediate and short-term periods. However, the effects on pain reduction and PPT diminish over time, suggesting a need for reapplication or combination with other interventions for sustained long-term benefits.